Salmonella spp no processamento tecnológico de tambatinga (Colossoma macropomum x Piaractus brachypomus) - Fernandes, Dandara Virginia Guia Semedo (2017)
Salmonella spp is a pathogen responsible for severe foodborne infection that can be introduced into the fish chain through inadequate handling and hygiene or in contact with contaminated water, since it is not a biological contaminant originally found in fish. Microbiological safety of fish is a concern of consumers, industries and regulatory agencies worldwide because fish can act as a vehicle for the transmission of Salmonella spp throughout the production chain, being an important category of food in international trade and are often exported to several countries. In addition, there is concern about the inadequate use of antibiotics in aquaculture as a result of increased isolation of resistant and multiresistant Salmonella serovars. In this context, the objective of this study was to study the dispersion dynamics and the antimicrobial resistance profile of Salmonella spp in the processing of uncooked Tambatinga (Colossoma macropomum x Piaractus brachypomus), to identify risk factors and potential routes of cross contamination. To this end, 30 fish were monitored during all processing steps in a fish slaughterhouse with the self-control programs implanted. A total of 120 samples were collected and submitted to bacteriological analysis, PCR and biochemical confirmation of Isolates that were also submitted to the antibiogram. Viable salmonella spp was identified in all steps of the flowchart, reception, post-wash with hyperchlorinated water, post evisceration / desquamation and in the cooling. The occurrence of Salmonella spp in the cooled fresh fish was 6.6% (2/30). We conclude that Salmonella spp is not part of the natural microflora of the tambatinga, however the fish contaminates in the culture tank and along the transport to the cold slaughterhouse, transfers the bacteria to other fish free from contamination through water and / or ice. The washing step with hyperchlorinated water performed at the fish reception stage should be considered a control point (PC) because Salmonella is not eliminated if the time and / or chlorine concentration is not applied correctly. Evisceration / desquamation are stages of processing that increase the risk of cross-contamination and dispersion of Salmonella spp in the slaughterhouse, however, the danger can be eliminated in the post-evisceration hyperchlorinated washing stage, this step should be considered a critical point of Control (PCC) and should be monitored frequently, since no further processing steps eliminate Salmonella spp from the product. All strains of Salmonella spp. (10) isolated along the slaughter line were sensitive to the main classes of antibiotics used in human and veterinary medical practice. This indicates that there is a high probability of clinical success if these antimicrobials are used to treat salmonellosis in humans, caused by possible contamination through the consumption of tambatinga.